KEBAIKAN UMUM DALAM AJARAN SOSIAL GEREJA - Xaverius Chandra (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
In this paper will elaborate the answer to the question what is being called by the Catholic Church’s Social Teaching on the general good? Here are shown the principles of the general good in the sphere of the state which are found in the Church’s Social Teaching. The goal of ASG is inseparable from the Church’s spir- itual mission to unite all people in God and among themselves, which demands contradicting what is contrary to this goal and supports that which supports the achievement of it.